A Socio pragmatic Study of Speech Act Realizations through Arabic Twitter (X) Discourse: Subjective Perspectives of Commenters - Fatimah Abdul Ghani Idrees (Hasanuddin University, 2025)
This study explores the realization of speech acts of (criticism, sarcasm, praise and so on) associated with Twitter or what is recently called (X) comments on the 2025 Arab summit in Iraq. This qualitative and descriptive study is drawing on synthesized framework of (Searle 1969 and Jucker 2024) speech act theory and draws its data from comments on Twitter. The comments were analyzed qualitatively to recognize not just their linguistic patterns and pragmatic meanings only, but also understanding their function in social media context enriched with stance-taking and multimodal cues (e.g., hashtags, emojis), taking into account cultural norms, social relationships and situational factors to reveal how individuals attribute actions. The findings reveal significant concerns about how Arabic people tend to combine the prevalence of assertive, religious expressions, directives imperatives, modals, performative verbs, rhetorical questions, emojis, and punctuation to convey socio-pragmatic intentions and assert their positions in public discussions. The study also highlights that speech acts surrounding the Arab Summit in Iraq reveal a complex interplay of pride, criticism, and persuasion in public social media discourse. Although certain comments rely on respectful language and expressions of collective identity, but critical voices often resort to irony, metaphor, and indirect challenges to dominant narratives. This diversity highlights not only how linguistic etiquette is negotiated in public settings, but also how socio-pragmatic norms, cultural values, and political ideologies shape the commenters ’opinions.